A systematic review of the proposed etiologies of the 2021–2022 outbreaks of pediatric acute hepatitis of unknown etiology - Lewis, Lauren; van Wylick, Carly; Mulder, Daniel J. (Frontiers in Pediatrics, 2023)
In April 2022, the World Health Organization (WHO) declared a global outbreak of acute hepatitis of unknown etiology (AHUE) with a high risk of severe outcomes, for which various etiologies have been proposed by the literature. This study examines primary reports of pediatric AHUE cases and summarizes the proposed etiologies. This systematic review collected and evaluated published peer-reviewed articles, official data, and clinical reports of AHUE cases that met the WHO working case definition. 19 hypothesized etiologies for AHUE were identified from 36 sources, which fell into eight categories. While human adenovirus (HAdV) infection, viral infection, and immunemediated responses were commonly suspected as causes of AHUE, no definitive etiology or epidemiological link has been established. However, recent evidence implicates adeno-associated virus-2 (AAV2) as a likely significant contributor. Conducting a comprehensive literature review following outbreaks is necessary for developing responsive strategies and protocols.